The structural and mechanical properties of the tamarind seed polysaccharide plasticized with deep eutectic solvent for food packaging - Md. Hilmi, Nurdamia Farhana; Ridzuan, Nurul Adlina; Norrizam, Nurnajihah; Azman, Nur Syamimi; Hashim, Faiezah; Wan Nafi, Atikah; Muhd Zailani, Nabilah Akemal (Universiti Teknologi MARA (UiTM), 2025)
Tamarind seed polysaccharides (TSP) exhibit significant potential as bioplastic films for food packaging, attributed to their biodegradability, renewability, cost-effectiveness, and biocompatibility. Nonetheless, the brittleness of TSP film, attributed to hydrogen bonding between the chains, will hinder its application. In this study, a deep eutectic solvent (DES) consisting of choline chloride and ethylene glycol was integrated into the TSP matrix at concentrations of 0.4 and 0.8 wt%, and the films were fabricated using the solvent casting technique. The structural and mechanical properties of the DES-plasticized TSP films were examined using Fourier transform infrared spectroscopy (FTIR) and tensile testing, respectively. The results indicated that the DES effectively enhanced the flexibility of TSP films by elevating the tensile strain value. The peak displacement in FTIR analysis demonstrated that TSP-DES interactions have markedly diminished the formation of hydrogen bonds among TSP chains. The ideal concentration of DES was 0.4 wt%, as this sample exhibited the maximum tensile strain of 10.35%. These findings underscore the potential of DES as an eco-friendly plasticizer for bioplastic films, warranting additional research on its thermal properties